Active chitosan/gum Arabic-based emulsion films reinforced with thyme oil encapsulating blood orange anthocyanins: Improving multi-functionality. (January 2023) - Zhao, Runan; Chen, Jin; Yu, Songfeng; Niu, Ruihao; Yang, Zhehao; Wang, Han; Cheng, Huan; Ye, Xingqian; Liu, Donghong; Wang, Wenjun
Abstract: Novel multifunctional food packaging was developed by incorporating blood orange anthocyanins (BOA) and thyme oil (TO) emulsion into a chitosan-gum Arabic film matrix. The basic properties, pH/volatile acid sensitivity, and functional characteristics of the multifunctional films were investigated. BOA solution illustrated significant color variations (from pink to violet to yellow) under different pH environments. The incorporation of anthocyanin and emulsion enhanced the UV–vis blocking, which made the film block almost all UV light. Meanwhile, the multifunctional film had stronger mechanical strength and thermal stability, whose elongation at break reached 76.1%, and the maximum degradation temperature raised to 305 °C. The incorporation of TO emulsion significantly enhanced the films' water resistance and made the water vapor barrier properties of the films reduce to 6.34 × 10 −11 g/Pahm. In addition, the multifunctional films exhibited noticeable changes of color in acid/alkaline environments within a short time interval, which could be easy to distinguish by naked eyes. The addition of emulsion made the multifunctional films slow-release of thyme oil, which significantly improved the antioxidant and dynamic antibacterial capacity of the films. Finally, the multifunctional films effectively extended the shelf-life of milk at 25 °C and visually monitored freshness through the color changes in real-time. This knowledge provides a new perspective and idea to develop multifunctional food packaging materials with preservation and monitoring functions. Graphical abstract: Image 1 Highlights: Blood orange anthocyanins (BOA) were used as pH-sensitive color indicators. Biopolymer-based films incorporating BOA and TO emulsion were fabricated. The color of films responded sensitively to acidic/alkaline environment. The films exhibited excellent antioxidant and antibacterial properties. The films can be used to prolong and visually monitor the food freshness.